Implementation of Sharia Economic Law Principles in Overcoming the Economic Impact of the Palestinian Israeli Conflict - Fattah, Abdul (Darul Yasin Al Sys, 2025)
This study discusses the implementation of Sharia Economic Law principles in overcoming the economic impact of the prolonged Palestinian-Israeli conflict. This conflict has not only destroyed the economic infrastructure in Palestine, but has also led to social difficulties and prolonged political instability. Through a qualitative approach and case study method, this study explores the role of zakat and waqf as short-term and long-term solutions in the recovery of the Palestinian economy. The results of the study show that zakat plays an important role in meeting the basic needs of people affected by conflict, while waqf supports the development of social infrastructure such as schools and hospitals. However, the implementation of these principles is still faced with challenges, especially related to economic blockades and political instability. Therefore, it is necessary to increase Islamic financial literacy, strengthen regulations, and international cooperation to maximize the role of Sharia Economic Laws in economic recovery in conflict areas.